The Role of Platelet Microparticle Associated microRNAs in Cellular Crosstalk - Xia, Luoxing; Zeng, Zhi; Tang, Wai Ho (Frontiers in Cardiovascular Medicine, 2018)
Platelet is an anucleate cell containing abundant messenger RNAs and microRNAs (miRNAs), and their functional roles in hemostasis and inflammation remain elusive. Accumulating evidence has suggested that platelets can actively transfer RNAs to hepatocytes, vascular cells, macrophages, and tumor cells. The incorporated mRNAs are translated into proteins, and miRNAs were found to regulate the gene expression, resulting in the functional change of the recipient cells. This novel intercellular communication opens up a new avenue for the pathophysiological role of platelet in platelet-associated vascular diseases. Therefore, understanding the underlying mechanism and identification of the platelet miRNAs involved in this biological process would provide novel diagnostic and therapeutic targets for cardiovascular diseases.